Application of Leadership to the Governance of the Sidoarjo Regency General Election Commission: Penerapan Kepemimpinan Terhadap Tata Kelola Komisi Pemilihan Umum Kabupaten Sidoarjo - Widya Kusuma Dewi; Wahyu Hananta Herlambang; Muhamad Vicky Saifudin N; Muhammad Ilham Tri H; Daffa Widyadhana; Hasan Ubaidillah (International Consortium of Education and Culture Research Studies, 2024)
General Background Regional democratic processes require robust institutional frameworks supported by competent administrative bodies to ensure fair and transparent public services. Specific Background The Sidoarjo Regency General Election Commission faces internal challenges regarding administrative experience, strategic communication, and competency, which potentially disrupt institutional reputation and operational management. Knowledge Gap While the theoretical necessity of administrative direction is well-documented, specific empirical observations on how localized executive actions translate into practical good governance principles remain underexplored. Aims This study investigates the application of administrative direction toward achieving good governance within a regional agency. Results Field observations reveal the implementation of targeted socialization for transparency, technical training for resource optimization, and employee reward systems for accountability. Furthermore, legal mitigation coordination establishes the rule of law within the organization. However, internal communication and public socialization protocols require significant structural improvements to prevent misinterpretations and optimize daily activities. Novelty This research maps specific human resource activities directly to core good governance indicators within a localized administrative setting. Implications Addressing the identified communication deficits is crucial for administrative leaders to solidify institutional integrity and guarantee transparent management. Highlights: Technical training programs and employee reward systems translate into administrative efficiency and institutional accountability. Legal mitigation meetings establish a strong structural foundation for the rule of law within the agency. Persistent internal communication deficits hinder optimal transparency and require immediate strategic improvements. Keywors: Good Governance, Leadership Application, Human Resource Management, Institutional Accountability, Administrative Transparency